Training assistant for industrial processes through augmented reality. - Romero López, Jonathan Alexis (2019)
This article presents an application of augmented reality, as a contribution to the industrial and education sector, through a technological tool for the assistance of operators in industrial processes. It facilitates the identification of equipment and instruments, granting the management and visualization of the parts constitutive of the elements of the process. Additionally, it guides in the calibration of instruments and the simulation of a closed loop control algorithm that allows control by regulation. Its development focuses on the recognition of equipment through a Smartphone for detect characteristic points of objects and image recognition, 3D modeling through CAD software and integration in a multiplatform, incorporation of animations and mathematical modeling of industrial processes that allows of the development of closed loop control algorithms. The tests performed on the augmented reality application demonstrated an easy handling and high interactivity with the user. The results provide greater knowledge in the operation and structure of the equipment, instrument and process. Finally, the results support the skills development for the tuning of PID controllers in industrial processes.